Neurological Outcome after Surgical Management of Tethered Cord Syndrome (Medical Forum Monthly, 2020)
Objective: To determine neurological outcome after surgical management of tethered cord syndrome.Study Design: Descriptive case series studyPlace and Duration of Study: This study was conducted at the Department of Neurosurgery, Punjab Institute of Neurosciences Lahore from April 2017 to October 2017.Materials and Methods: Fifty patients with tethered cord syndrome and radiographic evidence of tethered cord syndrome on magnetic resonance imaging of 10 years to 50 years with either gender and patients of meningocele or mylomeningocele with radiographic evidence of TCS on MRI were included. Patients previously operated for detethering of TCS and now presenting with recurrence or signs and symptoms of tethered cord syndrome and who have systemic illness (uncontrolled diabetes, hypertension, ischemic heart disease) and not fit for general anesthesia were excluded. Lumbosacral MRI and baseline investigations were done. Number of patients with back pain, disturbed motor function and urinary incontinence were noted. Laminectomy and detethering of spinal cord under operative microscope was done. Patients were followed for 6 month postoperatively for outcome variables i.e. improvement in back pain, motor function, urinary incontinence.Results: There were 30 (60.0%) male and 20 (40.0%) female patients with mean age was 36.6±10.7 years. Fifty (100.0%) patients had severe back pain at preoperatively and 50 (100.0%) patients had moderate pain postoperatively. Twelve (24.0%) patients had Grade–1 motor function and 38 (76.0%) patients had Grade-2 motor function preoperatively while 5 (10.0%) patients had Grade-3 motor function, 20 (40.0%) patients had Grade-4 motor function and 25 (50.0%) patients had Grade-5 motor function postoperatively. Fifty (100.0%) patients had urinary incontinence preoperatively and 33 (66.0%) patients had urinary incontinence and 17 (34.0%) patients had no urinary incontinence postoperatively. Thirty five (70.0%) patients had improvement in back pain, 18 (36.0%) patients had improvement in motor function and 17 (34.0%) patients had improvement in urinary incontinence at six month follow up.Conclusion: The back pain, motor function and urinary incontinence improve postoperatively in the majority of patients. The rate of symptomatic improvement was greatest for back pain, followed by motor, and then urinary improvement.